2003
DOI: 10.1016/s0009-2614(03)01094-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of high-quality single-walled carbon nanotubes on silicon and quartz substrates

Abstract: A new technique of synthesizing high-quality single-walled carbon nanotubes (SWNTs) directly on the surface of silicon and quartz substrates has been developed by means of the low-temperature catalytic CVD method using ethanol. The proposed method does not employ conventional deposition/sputtering for the mounting of catalytic metals on the substrates, but it adopts an easy and costless liquid-based dip-coat approach without need of support/underlayer materials that were often used in previous studies. The sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 24 publications
(46 reference statements)
3
147
0
Order By: Relevance
“…The proposed alcohol catalytic CVD (ACCVD) method can produce high-quality SWNTs when combined with appropriate catalysts and experimental procedures. Furthermore, it was recently demonstrated that high-quality SWNTs could be synthesized on a mesoporous-silica coated substrate [16] or directly on a solid substrate such as silicon or quartz [17,18]. Detailed comparisons of HiPco and ACCVD products are found in our recent papers [19,20], and the generation mechanism is discussed based on molecular…”
Section: Introductionmentioning
confidence: 99%
“…The proposed alcohol catalytic CVD (ACCVD) method can produce high-quality SWNTs when combined with appropriate catalysts and experimental procedures. Furthermore, it was recently demonstrated that high-quality SWNTs could be synthesized on a mesoporous-silica coated substrate [16] or directly on a solid substrate such as silicon or quartz [17,18]. Detailed comparisons of HiPco and ACCVD products are found in our recent papers [19,20], and the generation mechanism is discussed based on molecular…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Briefly, bimetallic Co/Mo catalyst particles were obtained by dip-coating Si substrates into separate Mo-acetate and Co-acetate solutions containing 0.01 wt.% of the respective metal species. After reducing the dip-coated substrate under flowing Ar/H 2 (3% H 2 ), the CVD chamber was evacuated and sealed.…”
Section: Methodsmentioning
confidence: 99%
“…However, simple and low-cost methods for SWNT synthesis are in dire need, and this can be achieved by combining the ACCVD method with a liquid-based catalyst loading method [30], impregnation and evaporation method, described as follows. …”
Section: Achievement Of Swntsmentioning
confidence: 99%
“…A liquid-dip coating method [30] is an easy and simple process to achieve with the result of many structures of SWNTs. The amount of catalysts deposited on the substrate surface can also be controlled by changing concentration of the catalyst.…”
Section: A Liquid Dip-coatingmentioning
confidence: 99%